The bounty hunter - Tennant, Andy, 1955-; Thorp, Sarah; Missick, Dorian, 1976-; Butler, Gerard, 1969-; Aniston, Jennifer; Malloy, Matt.; Baranski, Christine; Sony Pictures Home Entertainment (Firm); Columbia Pictures (Culver City, Calif. : Sony Pictures Home Entertainment, 2010)
Milo, a down-on-his-luck bounty hunter, gets his dream job when he is assigned to track down his bail-jumping ex-wife, reporter Nicole. He thinks it's an easy payday, until she gives him the slip to chase a lead on a murder cover-up. Milo soon realizes that nothing is ever simple with him and Nicole. As the two continue to one-up each other, they find themselves on the run for their lives. If they thought their promise to love, honor, and obey was tough, staying alive will be a lot tougher!
Release date: Jul. 13, 2010.
Title from disc label.
Director, Andy Tennant.
Dorian Missick, Gerard Butler, Jennifer Aniston, Matt Malloy, Christine Baranski.
Rating: PG-13; for sexual content including suggestive comments, language and some violence.
DVD, anamorphic widescreen; Dolby Digital 5.1.
Keywords: Bounty hunters -- Drama; Divorced people -- Drama; Fugitives from justice -- Drama; Feature films; Adventure films; Romantic comedy films; Videorecording; Video recordings for the hearing impaired